2016
DOI: 10.1007/s11524-016-0074-5
|View full text |Cite
|
Sign up to set email alerts
|

Congruence of Home, Social and Sex Neighborhoods among Men Who Have Sex with Men, NYCM2M Study

Abstract: Substantial literature demonstrates the influence of the neighborhood environment on health behaviors and outcomes. But limited research examines on how gay and bisexual men experience and exist in various geographic and virtual spaces and how this relates to their sexual behavior. New York City Men 2 Men (NYCM2M) was a cross-sectional study designed to identify neighborhood-level characteristics within the urban environment that influence sexual risk behaviors, substance use, and depression among men who have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Our study suggests that, among urban MSM, the places where they socialize, rather than those they inhabit, have a particularly important influence on anxiety (and potentially their levels of depression). The salience of social neighborhoods for MSM may be due to the lack of congruence between the places where MSM choose to live and socialize—this may lead MSM to spend relatively little time in their home neighborhoods [15]. This may reflect a broader issue that affects sexual minorities, who choose to socialize away from home when the neighborhood they inhabit is not supportive of sexual minorities or they are not out about their sexuality[36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study suggests that, among urban MSM, the places where they socialize, rather than those they inhabit, have a particularly important influence on anxiety (and potentially their levels of depression). The salience of social neighborhoods for MSM may be due to the lack of congruence between the places where MSM choose to live and socialize—this may lead MSM to spend relatively little time in their home neighborhoods [15]. This may reflect a broader issue that affects sexual minorities, who choose to socialize away from home when the neighborhood they inhabit is not supportive of sexual minorities or they are not out about their sexuality[36].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we have little information on the influence that other important contexts, including social and workplace environments, have on mental health. This is a particularly important concern for MSM, who often live and socialize in very different types of neighborhoods [15]. In prior work, we found that only one in five MSM sampled from New York City reported living and socializing in the same neighborhoods [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study using a politically-defined data (e.g., Census tracts) to characterize neighborhoods may diverge from the sociocultural boundaries assigned by residents to the same space. Moreover, recent data suggest that the characteristics of spaces where youth and MSM reside, work, socialize, and have sex may be quite different from each other (Duncan et al, 2014; Koblin, Egan, Nandi, Sang, Cerda, Tieu, Ompad, Hoober & Frye, 2016; Tobin et al, 2014). As a result, new methods that account for the role of diverse geospatial locations (e.g., home, sexual spaces, social spaces) on health outcomes are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…As described in detail previously[ 58 , 59 ], MSM from the main NYC M2M study were recruited in person using a modified venue-based, time-space sampling methodology and internet- and mobile application-based recruitment. They were eligible for the study if they self-reported biological male sex at birth; engaged in anal sex with a man in the past 3 months; at least 18 years of age; resided in New York City; communicated in English or Spanish; and were willing and able to give informed consent for the study.…”
Section: Methodsmentioning
confidence: 99%